Where is the Voice of Canada’s Voluntary Sector - Elson, Peter R. (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2008)
Voluntary organizations in general and charities in particular have consistently contended that government regulations and fear of contractual reprisals constrain their capacity to advocate for progressive social policies. This mticle focuses on the regulatory and institutional side of this equation and contends that advocacy constraints exhibited by charities may be less attributable to limits externally imposed by the federal government than they are to limitations on the institutional structure by which charities choose to organize. The Can& Revenue Agency was chosen because it has the widest influence on what is considered permissible political activities by charities across Canada. This study explored changes across three iterations of Canada Revenue Agency regulations concerning permissible political activities and resource allocation limits by registered charities. Between the release of Information Circular 78-3 in 1978, which was viewed by the voluntary sector as punitive and restrictive, and Political Activities CPS-022 in 2003, permissible political activities have been clarified and expanded. This study goes on to analyqe the institutional structure which characterized the voluntary sector and government when substantive policy dialogue developments took place across this twenty-five year period. This study concludes that the non-formal institutional structure characteristic of voluntary sector representation and reporting has influenced both the lack of legislative change and the nature and impact of sectoral advocacy. The voluntary sector in Canada would be well served by increasing its institutional structure formality and charities should work together to take full advantage of the potential new advocacy capacity available through Political Activities CPS-022. Les organismes be’ne’voles en ge’n&ral, et plus particuli2rement les organismes de bienfaisance, ont toujours pktendu que les r?glements gouvernementaux et la crainte de repre’sailles contractuelles limitent kur capacite’ h militer pour des politiques sociales pogressistes. L’article, qui s’attarde h l’aspect rkglementaire et institutionnel de cette e’quation, avance que les contraintes lie’es au militantisme pre’sente’es par les organismes de bienfaisance poumaient Ctre &vantage attribuables aux limites de la structure institutionnelle sous Iaquelle ces organismes choisissent d’exercer leurs activite’s qu’aux limites impose’es par le gouvernement fe’de’ral. L’auteur a choisi de se pencher sur llAgence du revenu du Canada parce qu’elle ewrce l’influence la plus importante sur la &finition des activitb politiques admissibles des organismes caritatifs au Canada. L’e’tude a examine’ les modifications apporte’es lors de trois p ksentations successives des r2glements de I’Agence du revenu du Canada relativement aux actiuite’s politiques admissibks et aux limites d’allocation de ressources des urganismes de bienfaisance. Entre le lancement de la Circulaire #information 78-3 en 1978, juge’e punitive et restrictive par le secteur be’ne’vole et communautaire, et celui de l’e’nonce’ de politique Activitks politiques CPS-022 en 2003, les actiuit6s politiques admissibles ont it6 clanfie’es et e’tendues. L’e’tude propose ensuite une analyse de h structure institutionnelle qui a caructe’rise’ la relation entre le secteur be’ne’vole et le gouvernement lorsque &S de’veloppements importants du dialogue relatif aux politiques sont survenus durant cette pkiode de 25 ans. L’auteur conclut que la structure institutionnelle informelle prope h la repre’sentation et h la production de rapports du secteur be’nkvole a exerce’ une influence tant sur le manque de changements d!ordre le’gislatif que sur la nature et l’imnpuct du militantisme de ce secteur. Le secteur be’ne’vole du Canada be’ne’ficierait d’une formalisation de sa structure institutionnelle, et les organismes caritatifs dewraient unir leurs efforts afin de profiter au maximum des nouvelles possibilite’s de militantisme offertes par l’e’nonce’ de politique Activitks politiques CPS-022.